Design and fabrication of low cost intelligent wheelchair (International Journal of Engineering and Computer Science, 2017)
A novel approach is proposed in this paper to impart intelligence to a low cost smart wheelchair based on embedded system. The sensors give the perceiving power to the wheelchair and scientific inference engine in the microcontroller gives the intelligent power of decision making and its implementation to the wheelchair. This approach is very effective as it does not involve the wastage of the computational and working power of PC/Laptop, rather by using the microcontroller based specific system we have saved the operating power as well as the cost involved in designing. This paper constitutes the circuit diagram of the proposed prototype of the intelligent wheelchair with the algorithms for decision making, table of comparison of features and the cost of the final product.